Global visibility for global health: Is it time for a new descriptor in Medical Subject Heading (MeSH) of MEDLINE/PubMed? - Ana Marušic´ (Edinburgh University Global Health Society, 2013)
Despite a large body of research in global health (almost 9000 articles published in PubMed until 2012), the term "global health" is not included in the Medical Subject Headings (MeSH) of the NLM - its controlled vocabulary thesaurus which NLM uses to index articles in MEDL INE. There are only 6 journals currently covered by PubMed which specialize in global health, including Journal of Global Health.